A safe supervisory flight control scheme in the presence of constraints and anomalies - Franz?, Giuseppe; Furfaro, Angelo; Mattei, Massimiliano; Scordamaglia, Valerio (Zielona Góra: Uniwersytet Zielonogórski)
In this paper the hybrid supervisory control architecture developed by Famularo et al. (2011) for constrained control systems is adopted with the aim to improve safety in aircraft operations when critical events like command saturations or unpredicted anomalies occur. The capabilities of a low-computational demanding predictive scheme for the supervision of non-linear dynamical systems subject to sudden switchings amongst operating conditions and time-varying constraints are exploited in the flight control systems framework.
Keywords: supervisory control; command governor; failures; fault tolerant control; flight control